2024
DOI: 10.1186/s40594-024-00479-2
|View full text |Cite
|
Sign up to set email alerts
|

Beyond performance, competence, and recognition: forging a science researcher identity in the context of research training

Mariel A. Pfeifer,
C. J. Zajic,
Jared M. Isaacs
et al.

Abstract: Background Studying science identity has been useful for understanding students’ continuation in science-related education and career paths. Yet knowledge and theory related to science identity among students on the path to becoming a professional science researcher, such as students engaged in research at the undergraduate, postbaccalaureate, and graduate level, is still developing. It is not yet clear from existing science identity theory how particular science contexts, such as research trai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Providing an option which allowed participants to make clear that they have not received a particular form of training may have clarified this, particularly in light of recent work by Wilson et al (2023) who identified that peers can help build a 'researcher' identity through the sharing of experiences and perspectives including through the use of online platforms. Mentoring has also been highlighted as important in the development of a scientific identity, which has been linked to a researchers’ career trajectory, although this mentoring mostly focuses on the student-supervisory mentoring relationship ( Pfeifer et al , 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Providing an option which allowed participants to make clear that they have not received a particular form of training may have clarified this, particularly in light of recent work by Wilson et al (2023) who identified that peers can help build a 'researcher' identity through the sharing of experiences and perspectives including through the use of online platforms. Mentoring has also been highlighted as important in the development of a scientific identity, which has been linked to a researchers’ career trajectory, although this mentoring mostly focuses on the student-supervisory mentoring relationship ( Pfeifer et al , 2024 ).…”
Section: Discussionmentioning
confidence: 99%